Design, optimization and characterization of glutathione loaded-alginate microspheres for topical antiaging - Dewi Melani Hariyadi; Noorma Rosita; Asti Rahayu (GarVal Editorial Ltda., 2019)
Context: Glutathione in the reduced form (GSH) is the predominant intracellular form, which acts as a strong antioxidant. However, it has low skin permeability due to the high hydrophilicity. Hence, the objective of this study was to prepare GSH by using microspheres delivery system and adding surfactant to overcome the barrier function of the skin. Aims: To investigate the effect of polymer and surfactant on the characteristics and release profile of GSH-alginate microspheres. Methods: GSH-alginate microspheres were prepared using ionotropic gelation method by aerosolisation. A randomized full factorial design was applied to prepare four different formulations of glutathione loaded alginate microspheres. Design was applied for all formulations to study about effect of independent variables of polymer and crosslinker on the entrapment efficiency (EE), drug loading (DL), particle size, yield, and in vitro drug release profile. For release study, microspheres formulas were also compared to microspheres, which applied into gel base. Results: The GSH-alginate microspheres had a high EE ranging from 34.74 ± 0.07% to 56.63 ± 0.36%, with small particle sizes ranging from 1.89 ± 0.03 µm to 2.42 ± 0.08 µm, and drug loading ranging from 5.72 ± 0.05% to 6.23 ± 0.02%. The kinetic analysis of all release profiles was found to follow Higuchi's diffusion model. EE, DL, particle size, and yield variables had a significant effect on the dependent variables (p<0.05), and flux had no significant effect on the dependent variables (p>0.05). Conclusions: All formulas produced high yield and encapsulation efficiency and small size particles. From the 22 randomized full factorial design, there was showed that the combination of the use of surfactant and polymer concentration significantly affected DL and EE.